2022
DOI: 10.3390/ijerph19095418
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Telemedicine Outpatient Practice Diagnoses Set during the First COVID-19 Pandemic Lockdown—Individual Observation

Abstract: The COVID-19 pandemic has caused a substantial intensification of the telemedicine transformation process in orthopedics since 2020. In the light of the legal regulations introduced in Poland, from the beginning of the SARS-CoV-2 pandemic, physicians, including orthopedic surgeons, have had the opportunity to conduct specialist teleconsultations. Teleconsultations increase epidemiological safety and significantly reduce the exposure of patients and medical staff to direct transmission of the viral vector and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…9,79 It has also been reported that awareness and knowledge regarding the VVs disease and its contributory factors can play a role in the intervention of the VVs ailment. 88 Our research has few study limitations. First, the primary focus of the study was only VVs among the six classes of CEAP classification that later become more complicated, severe, and painful if undiagnosed or neglected, and affects an individual's life quality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…9,79 It has also been reported that awareness and knowledge regarding the VVs disease and its contributory factors can play a role in the intervention of the VVs ailment. 88 Our research has few study limitations. First, the primary focus of the study was only VVs among the six classes of CEAP classification that later become more complicated, severe, and painful if undiagnosed or neglected, and affects an individual's life quality.…”
Section: Discussionmentioning
confidence: 94%
“… 9 , 79 It has also been reported that awareness and knowledge regarding the VVs disease and its contributory factors can play a role in the intervention of the VVs ailment. 88 …”
Section: Discussionmentioning
confidence: 99%
“…Because of the high granularity of the data collected, complications and deviations from the expected recovery path can potentially be detected earlier than with practice visits alone, allowing clinicians to manage patients by exception rather than following a standardized trajectory for all patients. In addition, remote patient monitoring can be particularly valuable in conditions such as the recent COVID-19 pandemic, enabling continued patient monitoring while limiting potential disease-transmitting contacts (e.g., Glinkowski 2022;Haider et al 2022;Muller et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, over the last decade, scientists and clinical practitioners have already collected a lot of evidence that telemedicine has helped to solve a great number of problems resulting, inter alia, from epidemiological emergencies, inducing the requirement of social distance. Moreover, at the same time, it turned out to be a possible additional, acceptable, and effective form of helping patients in specific circumstances [ 3 , 4 ]. By being an application of telematics in medicine, telemedicine includes technologies aimed at collecting information, analyzing, sending, processing, presenting it, and sharing it with stakeholders.…”
Section: Introductionmentioning
confidence: 99%